Linear Regression Approach for Porosity and Permeability Calculations from Well Logs: A Case Study in NW Bonaparte Basin, Australia - Ahmed Mohamed Ahmed Salim, Osama Akhtar Janjua, Ali Wahid, Aruba, . (2015)
Information of the rock properties can be observed with the help of core samples and well logs. This outcome was averaged into effective large scale information by using statistical techniques which help to find the spatial arrangement of these properties. Geostatistics or statistical sciences is the approach which is based on the studies of spatial and temporal phenomena. It depends on the trend of spatial relationships to model available information of variable (s) at unobserved and unsampled locations